2020
DOI: 10.3389/fphys.2020.01045
|View full text |Cite
|
Sign up to set email alerts
|

Increased Beat-to-Beat Variability of T-Wave Heterogeneity Measured From Standard 12-Lead Electrocardiogram Is Associated With Sudden Cardiac Death: A Case–Control Study

Abstract: Introduction The prognostic significance of beat-to-beat variability of spatial heterogeneity of repolarization measured from standard 12-lead ECG is not well-understood. Methods We measured the short-term variability of repolarization parameters, such as T-wave heterogeneity in leads V4–V6 (TWH) and QT interval (QT), from five consecutive beats of previously recorded standard 12-lead ECG in 200 victims of unexpected sudden cardiac death (SCD) confirmed to be due to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It was however recently found that spleen baseline volume was greater in experienced mountaineers going to climb Mt Everest, than in Mt Everest Base Camp trekkers (Schagatay et al 2020 ), suggesting that spleen function is important for successful climbing at high altitude. It was also recently reported that larger spleens and more powerful contractions were present in the Sherpa population of high altitude origin, compared to Nepali lowlanders (Holmström et al 2020 ). A difference between Sherpas currently residing high and low, respectively, was also observed, suggesting that not only genetic factors but also exposure to hypoxia may determine spleen size (Holmström et al 2020 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It was however recently found that spleen baseline volume was greater in experienced mountaineers going to climb Mt Everest, than in Mt Everest Base Camp trekkers (Schagatay et al 2020 ), suggesting that spleen function is important for successful climbing at high altitude. It was also recently reported that larger spleens and more powerful contractions were present in the Sherpa population of high altitude origin, compared to Nepali lowlanders (Holmström et al 2020 ). A difference between Sherpas currently residing high and low, respectively, was also observed, suggesting that not only genetic factors but also exposure to hypoxia may determine spleen size (Holmström et al 2020 ).…”
Section: Discussionmentioning
confidence: 81%
“…It was also recently reported that larger spleens and more powerful contractions were present in the Sherpa population of high altitude origin, compared to Nepali lowlanders (Holmström et al 2020 ). A difference between Sherpas currently residing high and low, respectively, was also observed, suggesting that not only genetic factors but also exposure to hypoxia may determine spleen size (Holmström et al 2020 ).…”
Section: Discussionmentioning
confidence: 81%
“…Clinically, T-wave alternans (TWA) is the most common form of cardiac electrical alternans. It is associated with the dispersion of repolarization and can be used as a biomarker to predict malignant arrhythmias and sudden cardiac death (SCD; Hekkanen et al, 2020 ). At the cellular level, TWA is measured as every-other-beat variations in action potential morphology (AP alternans) and/or in the cytosolic calcium transient (CaT alternans) at a constant stimulation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In the contemporary era of dynamic surface electrocardiography, a formidable challenge is quantifying spatiotemporal repolarization heterogeneity with sufficient fidelity to image the arrhythmogenic myocardial substrate and thereby provide indices for a patient's risk of arrhythmic death (Laguna et al, 2016). Hekkanen et al (2020) performed a large case-control study of 200 victims of sudden cardiac death (SCD) due to autopsy-proven coronary artery disease, who were age-, and sex-matched to controls with angiographically-confirmed coronary artery disease from the ARTEMIS database. A comprehensive analysis of their 12-lead ECGs within a mean of 1.8 months from SCD was performed to evaluate several measures of spatial repolarization heterogeneity, including an assessment of their temporal variability based on the standard deviation (SD) of each measure over 5 consecutive beats.…”
mentioning
confidence: 99%
“…In a 5600 subject cohort study with 12-lead ECGs, TWH in the left precordial leads (V4-V6) independently predicted SCD [adjusted Hazard ratio 1.4 (95th confidence interval 1.2-1.8) per increment of one standard deviation] (Kenttä et al, 2016). In contrast, Hekkanen et al (2020) computed TWH from a single beat in order to derive TWH-SD from 5 consecutive beats. This approach necessitates high quality beat-to-beat ECG recordings and there was no assessment of noise or reproducibility by the authors.…”
mentioning
confidence: 99%